A functional discrete method (FD-method) for solving the Cauchy problem for a nonlinear Klein–Gordon equation - Makarov, V. L.; Dragunov, D.V.; Sember, D.A. (Reports of the National Academy of Sciences of Ukraine, 2014)
We propose a functional-discrete method for solving the Cauchy problem for a nonlinear Klein–Gordon equation. Sufficient conditions for the superexponential convergence of this method are obtained. The obtained theoretical results are illustrated by a numerical example.